P-P57 The first experience of intraoperative radiotherapy for pancreatic cancer in the UK. (16th December 2021) - Bhome, Rahul; Dimitrios, Karavias; Tom, Armstrong; Hamady, Zaed; Ali, Arshad; John, Primrose; Pearce, Neil; Arjun, Takhar
Abstract: Background: Intraoperative radiotherapy (IORT) involves giving a targeted single fraction of high dose radiation to the resection bed. The main advantages are exclusion of vulnerable structures from the radiation field and ability to direct the electron beam to threatened margins. IORT in pancreatic cancer is not new, with Japanese centres reporting series from the 1970s. Early reports were exciting, suggesting that IORT was useful in reducing visceral pain, achieving local control and improving survival in locally advanced and unresectable patients. However, paucity of randomised trials in the ensuing decades has limited its widespread adoption. Methods: With funding from the PLANETS charity (www.planetscharity.org ), University Hospitals Southampton acquired a Mobetron 2000 linear accelerator (IntraOp, USA) in 2016. Testing was done at the National Physical Laboratory (Teddington, UK) over two months to collect beam data and ensure consistency in treatment delivery. Staff training included visits to the Heidelberg Cancer Centre and several dry runs. Inclusion criteria were: (i) patients with pancreatic head adenocarcinomas; (ii) threatened vascular margins; (iii) WHO performance status 1-2; (iv) no evidence of distant metastasis. Results: Nineteen patients had pancreaticoduodenectomy (traditional or pylorus preserving) combined with IORT. Median age was 66 (42-81) years. Median ASA grade was 2 (2-3). 16/19 had locally advanced pancreatic cancer and 18/19 had neoadjuvant chemotherapy. Median IOERT dose was 15 (10-15) Gy, energy 7.5 (6-12) MeV, to a mean depth of 1.6 +/- 0.8 cm, with median cone size 5 (4-6) cm and bevel angle 15 (0-30) degrees. All tumours were pT1-T3 and 10/19 had positive regional nodes. 10/19 were R1 resections, with 4/19 specimens exhibiting vascular invasion and 6/19 perineural invasion. Mean operating time (including IOERT) was 534 +/- 77 min. Median length of stay was 8.5 (6-41) days. 30-day mortality was zero. 6/19 patients had post-operative complications (Clavien-Dindo 1-2 only), with clinically detectable pancreatic fistula in 1/19. Conclusions: This is the first UK experience of IORT for pancreatic cancer, showing that this treatment modality is safe and feasible. With the appropriate expertise, an IORT service can be implemented within 12 months of acquiring the Mobetron system. We hope that these data will encourage other UK and European HPB units to consider setting up regional IORT services, such that larger scale prospective trials can be initiated to demonstrate its efficacy.